Creating Memorandums of Understanding/Agreement with Affiliate Organizations of 4-H - Marilyn N. Norman; Joy C. Jordan (EDIS)
4H2.5, an 8-page factsheet by Marilyn N. Norman and Joy C. Jordan, explains how 4H can effectively and productively work together with other nonprofit groups by drafting Memorandums of Understanding to guide the process and make it work smoothly. Includes 3 sample Memorandums. Published by the UF Department of Family, Youth and Community Sciences, January 2007.